Measuring Service Quality and its Relationship with Customer Patronage at a Car Dealership in South Africa - Garg, Ajay K. (Indian Journal of Marketing, 2018)
This study assessed the dimensions of service quality within a car dealership in Gauteng province in South Africa and further studied the relationship between the service quality dimensions on customer patronage. Valid responses using survey monkey were received from 74 customers out of a total of 750 who visited the dealership. Results indicated that there were negative gap scores for four out of the five service quality dimensions, these being reliability, responsiveness, assurance, and empathy. The demographic profile (age, gender, income) affected perceived and expected service quality. Regression analysis revealed that reliability and assurance were positively related with customer patronage, while the tangibles - responsiveness and empathy did not have any statistically significant relationship with customer patronage.